Analisis Penerapan Strategi Komunikasi Efektif dalam Marketing Public Relations di CV Inti Motor Solo - Yuliana, Margaretha Evi; Maharani, Chicha Adita; Khoirudin, Ibnu (Neolectura, 2024)
The development number of motorize vehicle users is increasing. This makes the automotive business have promising business prospects. The high level of business competition requires each company to create the best business strategy to win market competition. This research aims to determine the implementation of effective communication strategies in marketing public relations at CV. Inti Motor Solo. This research was conducted qualitatively descriptively and data was collected through observation and interview at CV. Inti Motor Solo. The results of the research indicate that marketing public relations activities at CV. Inti Motor Solo are still focused on activities to build consumer loyalty. Marketing Public relations activities carried out include the installation of company identity banners, information services, and consumer loyalty programs. Overall, marketing public relations activies at CV. Inti Motor Solo have implemented effective communication strategies well which include respect, emphaty, audible clarity, and humble.